Room temperature synthesis of reduced TiO2 and its application as a support for catalytic hydrogenation. Issue 8 (16th January 2017) - Zhang, Miao; Pei, Qijun; Chen, Weidong; Liu, Lin; He, Teng; Chen, Ping
Abstract : Reduced TiO2 (TiO2− x ) with a controllable reduction degree was synthesized, which can promote the catalytic hydrogenation of N-heterocycle as a catalyst support. Abstract : Reduced TiO2 (TiO2− x ) materials have attracted increasing attention due to their large solar absorption and high photo-activity. However, their synthesis procedures usually involve harsh conditions, such as high temperature and/or high pressure. Herein, a facile solid ball-milling method for the synthesis of TiO2− x under ambient conditions was developed. By using finely dispersed Na/NaCl powders as the reducing agent and TiO2 (P25, Degussa) as the precursor, a series of TiO2− x of 20–30 nm with a controllable reduction degree can be successfully synthesized through adjusting the reaction conditions. The surface area of TiO2− x is much larger than that of pristine TiO2, showing its great potential as a catalyst support in chemical reactions. Our experimental results show that uniform Ru particles with particle size less than 1 nm can be well dispersed on the surface of the TiO2− x due to the enhanced surface area and plenty of oxygen vacancies in TiO2− x . As a result, Ru/TiO2− x exhibited superior activity upon catalytic hydrogenation of N -methylpyrrole in comparison with Ru/TiO2 .